2022
DOI: 10.1111/2041-210x.13866
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic flowering plant collections embody the extended specimen

Abstract: The widespread digitization of natural history collections, combined with novel tools and approaches is revolutionizing biodiversity science. The ‘extended specimen’ concept advocates a more holistic approach in which a specimen is framed as a diverse stream of interconnected data. Herbarium specimens that by their very nature capture multispecies relationships, such as certain parasites, fungi and lichens, hold great potential to provide a broader and more integrative view of the ecology and evolution of symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…They found that nests tended to be larger in colder climates and suggest that the ability to alter nest structure in response to climate change could influence species persistence. In Methods in Ecology and Evolution , Teixeira‐Costa et al (2023) review what is known about parasitic plant specimens in herbaria around the world. Impressively, there are upwards of 1,000,000 records (476,000 of which are georeferenced) of more than 4300 species.…”
Section: The Impact Of Global Change On Phenotypesmentioning
confidence: 99%
“…They found that nests tended to be larger in colder climates and suggest that the ability to alter nest structure in response to climate change could influence species persistence. In Methods in Ecology and Evolution , Teixeira‐Costa et al (2023) review what is known about parasitic plant specimens in herbaria around the world. Impressively, there are upwards of 1,000,000 records (476,000 of which are georeferenced) of more than 4300 species.…”
Section: The Impact Of Global Change On Phenotypesmentioning
confidence: 99%
“…Thus, despite including a limited number of samples, our analysis corroborates the interpretation of Mitrastemonaceae as specific to hosts in the Fagaceae. Future analyses using methods such as DNA barcoding will be especially useful in cases where host identity is uncertain due to insufficient collection of host material (Pelser et al, 2016; Teixeira‐Costa et al, 2022). These methods are of increasing importance in the case of parasite species associated with the roots of their host plants, including not only Mitrastemonaceae but also euphytoid or obligate root parasites, for which careful examination and extensive excavation of roots are required for the correct host identification.…”
Section: Host Rangementioning
confidence: 99%
“…Allied to this peculiar lifestyle, the muted colors and small flower size ranging from 3 to 5 cm tall (Makino, 1911; Meijer & Veldkamp, 1993) make these plants easy to overlook among the leaf litter (Jochems, 1928). This may explain the small number of herbarium records (<150 specimens) available online for both M. matudae and M. yamamotoi in collections worldwide (Teixeira‐Costa et al, 2022). In turn, this scarcity of records could be why populations appear to be fragmented across the disjunct geographical distribution of the family (Figure 1e).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step would be the modernisation of the collection, taking advantage of modern technologies that allow inclusion of additional related information besides the preserved species following the extended specimen concept ( Lendemer et al 2019 ), which expands the possibilities of research and education that can be achieved with biological collections by including extra information that is usually lost after specimen preservation (e.g. tissue samples for DNA extraction, chemical profiles and ecological context information; Teixeira-Costa et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%